Caspr1 Facilitates sAPPα Production by Regulating α-Secretase ADAM9 in Brain Endothelial Cells - Tang, Shi-Yu; Liu, Dong-Xin; Li, Yuan; Wang, Kang-Ji; Wang, Xia-Fei; Su, Zheng-Kang; Fang, Wen-Gang; Qin, Xiao-Xue; Wei, Jia-Yi; Zhao, Wei-Dong; Chen, Yu-Hua (Frontiers in Molecular Neuroscience, 2020)
The expression of Caspr1 (contactin-associated protein 1) in brain microvascular endothelial cells (BMECs), one of the major cellular component of the neuro-vascular unit, has been revealed recently. However, the physiological role of Caspr1 in BMECs remains unclear. We previously reported the non-amyloidogenic processing of amyloid protein precursor (APP) pathway in the human BMECs (HBMEC). In this study, we found Caspr1 depletion reduced the levels of soluble amyloid protein precursor α (sAPPα) in the supernatant of HBMECs, which could be rescued by expression of full-length Caspr1. Our further results showed that ADAM9, the α-secretase essential for processing of APP to generate sAPPα, was decreased in Caspr1-depleted HBMECs. The reduced sAPPα secretion in Caspr1-depleted HBMECs was recovered by expression of exogenous ADAM9. Then we identified that Caspr1 specifically regulates the expression of ADAM9, but not ADAM10 and ADAM17, at transcriptional level by NF-κB signaling pathway. Caspr1 knockout attenuated the activation of NF-κB and prevented the nuclear translocation of p65 in brain endothelial cells, which was reversed by expression of full-length Caspr1. The reduced sAPPα production and ADAM9 expression upon Caspr1 depletion was effectively recovered by NF-κB agonist. The results of luciferase assays indicated that the NF-κB binding sites is located at -859 bp to -571 bp of ADAM9 promoter. Taken together, our results demonstrated that Caspr1 facilitates sAPPα production by transcriptional regulation of α-secretase ADAM9 in brain endothelial cells.